Japanese Encephalitis Vaccine Generates Cross-Reactive Memory T Cell Responses to Zika Virus in Humans - Ran Wang; Meng Zhang; Linlin Zhang; Mengjia Liu; Chao Shan; Jing An; Zhengde Xie (Journal of Tropical Medicine)
Objective. Zika virus (ZIKV) and Japanese encephalitis virus (JEV) are mosquito-borne flaviviruses with sequence homology. ZIKV circulates in some regions where JEV also circulates, or where JE vaccination is used. Cross-immunity between flaviviruses exists, but the precise mechanisms remain unclear. We previously demonstrated that T cell immunity induced by the live-attenuated Japanese encephalitis (JE) SA14-14-2 vaccine conferred protective immunity against ZIKV infection in mice, which could even bypass antibody-dependent enhancement. However, the role of T cell immune, especially memory T cell subsets, in cross-reactive immune responses between JE vaccine and ZIKV in humans has not been reported. Methods. We examined central and effector memory CD4+ and CD8+ T cell (TCM and TEM) responses (including degranulation, cytokines, and chemokines) in the presence of JEV and ZIKV, respectively, by using qualified peripheral blood mononuclear cell samples from 18 children who had recently received a two-dose course of JE vaccine SA14-14-2 as well as seven children without JE vaccination. Results. Cross-reactive CD8+ TCM in response to ZIKV was characterized by secretion of IFN-γ, whereas CD8+ TEM did not show significant upregulation of functional factors. In the presence of ZIKV, IFN-γ and TNF-α expression was upregulated by CD4+ TEM, and the expression signature of CD4+ TCM is more cytotoxic potential. Conclusions. We profiled the cross-reactive memory T cell responses to ZIKV in JE vaccine recipients. These data will provide evidence for the mechanism of cross-reactive memory T cell immune responses between JEV and ZIKV and a more refined view of bivalent vaccine design strategy.